2003
DOI: 10.1177/000348940311200913
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Distribution of Waardenburg Syndrome

Abstract: To clarify the multiracial occurrence of Waardenburg syndrome, we present a case series and literature review. A computerized review of the English-language literature was conducted to assess the distribution of reported occurrences of Waardenburg syndrome in populations around the world. We detail the clinical features of 2 family cohorts: one of Western European origin and the other from South Asia. A computerized literature review found sporadic cases of the syndrome in many ethnic groups, including Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 14 publications
(2 reference statements)
0
71
0
2
Order By: Relevance
“…4B). This congenital syndrome stems from defects in the developing neural crest and is characterized by craniofacial dysmorphology, abnormal pigmentation, and hearing loss [in fact, it accounts for 2-5% of cases of human deafness (27)]. In particular, this phenolog suggested that a set of three vesicle trafficking genes involved in directing plant growth in response to gravitational cues might also serve to direct neural crest cell migration and differentiation in developing animal embryos.…”
Section: Human/arabidopsis Phenologs Predict Vertebrate Regulators Ofmentioning
confidence: 99%
“…4B). This congenital syndrome stems from defects in the developing neural crest and is characterized by craniofacial dysmorphology, abnormal pigmentation, and hearing loss [in fact, it accounts for 2-5% of cases of human deafness (27)]. In particular, this phenolog suggested that a set of three vesicle trafficking genes involved in directing plant growth in response to gravitational cues might also serve to direct neural crest cell migration and differentiation in developing animal embryos.…”
Section: Human/arabidopsis Phenologs Predict Vertebrate Regulators Ofmentioning
confidence: 99%
“…WS is an autosomal dominant auditorypigmentation disorder in humans (1 per 40,000 live births) that accounts for 2% of all cases of congenital deafness (12). Several genes have been implicated in the four clinical varieties of WS: Mutations in PAX3 cause WS type 1 and type 3 (13,14) and mutations in SOX10, EDNRB, or EDNR3 cause WS type 4 (15)(16)(17).…”
mentioning
confidence: 99%
“…Indeed, the authors have discovered a mutation in the dog SILV gene that is responsible for merle, a color patterning in the coat of various canine breeds. Strikingly, merle dogs exhibit auditory and ophthalmologic abnormalities similar to those observed for the human auditorypigmentation disorder Waardenburg syndrome, which accounts for 2-5% of all human cases of congenital deafness (5).…”
mentioning
confidence: 68%